1992
DOI: 10.1111/j.1365-2621.1992.tb05500.x
|View full text |Cite
|
Sign up to set email alerts
|

Blackberry Juice and Wine: Processing and Storage Effects on Anthocyanin Composition, Color and Appearance

Abstract: Blackberry wine was made from thawed fruit (Evergreen variety) by fermentation of pulp, depectinized juice, and high-temperature shorttime (HTST)-treated and depectinized juice. The effects of fining and storage on pigment composition, color and appearance were investigated. Seven anthocyanin pigments (cyanidin-3-glucoside, cyanidin-3-rutinoside, a xylose-cyanidin derivative, two acylated cyanidin derivatives, cyanidin and a polymeric derivative) were detected in the juices and wines by HPLC. Cyanidin-3-glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
66
2
5

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 13 publications
17
66
2
5
Order By: Relevance
“…This finding agreed with early studies who found SO 2 could preserve anthocyanin and improve color quality of final products (Skrede et al, 2000;Lee et al, 2002;Rommel et al, 1992;Rossi et al, 2003;Fang et al, 2006).…”
Section: Comparing 95℃supporting
confidence: 82%
“…This finding agreed with early studies who found SO 2 could preserve anthocyanin and improve color quality of final products (Skrede et al, 2000;Lee et al, 2002;Rommel et al, 1992;Rossi et al, 2003;Fang et al, 2006).…”
Section: Comparing 95℃supporting
confidence: 82%
“…In addition, Clark and Finn [5] recorded that SSC of at least 10% provides for a "sweet" eating experience for fresh blackberries. The SSC assessment is not only important for juice quality evaluation, but for determining also the suitability of cultivars for blackberry winemaking [36]. Titratable acidity also significantly varied among blackberry cultivars, being higher in 'Čačanska Bestrna', and lower in 'Navaho'.…”
Section: Soluble Solids Content and Acidity Levelmentioning
confidence: 99%
“…Hence, it has been suggested that anthocyanin fi ngerprints of the wine relative to grapes might be the consequence of diff erent extraction rates of anthocyanins, or some degradation reactions that occur during winemaking. For example, the instability of cyanidin-3-glucoside during fermentation observed in blackberry (15) and red raspberry wines (20) is considered to be responsible for the lower concen tration of this compound in the wines compared to the fruits. In addi tion, the pigment analysis of the strawberry wine conducted earlier showed a signifi cant decrease of anthocyanin content aft er fermentation, where only 3-9 % of anthocyanins present in fruits were retained, as well as their progressive decrease throughout the storage (40).…”
Section: Individual Phenolic Compounds Of Fruit Winesmentioning
confidence: 99%
“…Wide concentration ranges of individual phenolic compounds that were obtained within a particular fruit wine could be att ributed to the eff ect of variety (11), geographical origin (13), maturity (40), winemaking technology (16)(17)(18)21,35) and phenolic changes that occur during ageing (15,20) and, moreover, to the synergistic eff ect of the mentioned factors. Fruit wines showed qualitative and quantitative diff erences in the profi le of phenolic acids (Table 2).…”
Section: Individual Phenolic Compounds Of Fruit Winesmentioning
confidence: 99%
See 1 more Smart Citation